Toward a Critical Phenomenology of Health - Talia Welsh (Philosophies, 2026)
Phenomenologies of health remain relatively infrequent compared to phenomenologies of illness. This paper addresses this lack by first summarizing some key elements of phenomenologies of health. First, health typically resides in the background of our experience. Second, health requires a creative, adaptive capacity to life’s variations. The paper then explores prescriptive critical phenomenology of health. It highlights key elements of treatment to produce health that avoid a reductive medicalized approach. The paper examines the social and political determinants of health as key elements of a critical approach to health. Finally, it argues for support of public health as essential to questions of health to counteract the contemporary view of health as solely a personal, rather than contextual, matter.